Pengaruh Stres Kerja, Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Amak Firdaus Utomo Kota Probolinggo - Basori, Saipullah; Yatiningrum, Agung; Widayanto, Mutinda Teguh (Universitas Panca Marga, 2024)
This research was conducted at PT Amak Firdaus Utomo, Probolinggo City with the aim of this research being to examine the influence of work stress, workload and work environment on employee performance at PT. Amak Firdaus Utomo, Probolinggo City. The population in this study were employees of PT Amak Firdaus Utomo, Probolinggo City, totaling 393 employees. The sample in this study uses the technique used in this research is the simple random sampling technique. According to Dewi&Pertiwi in (Devi et al, 2023)